Viability of seed balls for large-scale restoration of native plant communities in New Zealand - James W. Griffiths; Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; Jennifer Alderton-Moss; Karin van der Walt; Anja McDonald; Kirsty Moran (New Zealand Journal of Botany, 2025)

Physical properties of seed ball formulations - Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; James W. Griffiths (New Zealand Journal of Botany, 2025)

Covalently linked phosphate monoesters on alpha-polyglucans reduce substrate affinity of branching enzymes - Victoria Butler; Hanan Shaaban; Lilya Nasanovsky; Jessica K.V. White; Owen Hebb; Lynne Jones; Megan Whiting; Neije Mukherjee-Roy; Alina P. Montalbano; Carmen Elena Machado Vides; Felix Nitschke; Ian J. Tetlow (Carbohydrate Polymers, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

In Forest and Intact: Designating Future Use of Family-Forest-Owned Land - Marla Markowski-Lindsay; Paul Catanzaro; Kathleen Bell; David Kittredge; Ezra Markowitz; Jessica Leahy; Brett Butler; Anita Milman; Shorna Allred (Journal of Forestry, 2018)

Standardized capture rates of the endangered American burying beetle, Nicrophorus americanus Olivier (Coleoptera: Silphidae) using different trap protocols - Stephanie R. Butler; Robert Harms; Kerri Farnsworth-Hoback; Keith Koupal; Jessica Jurzenski; W. Wyatt Hoback (Journal of Insect Conservation, 2013)

Redox-active antioxidant modulation of lipid signaling in vascular endothelial cells: vitamin C induces activation of phospholipase D through phospholipase A2, lipoxygenase, and cyclooxygenase - Emily Steinhour; Shariq I. Sherwani; Jessica N. Mazerik; Valorie Ciapala; Elizabeth O’Connor Butler; Jason P. Cruff; Ulysses Magalang; Sampath Parthasarathy; Chandan K. Sen; Clay B. Marsh; Periannan Kuppusamy; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2008)

The composition and importance of the phytoneuston in two floodplain lakes in south-eastern Australia - Jessica Butler; Roger Croome; Gavin N. Rees (Hydrobiologia, 2007)

Structure and membrane affinity of new amphiphilic siderophores produced by Ochrobactrum sp. SP18 - Jessica D. Martin; Yusai Ito; Vanessa V. Homann; Margo G. Haygood; Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2006)